2017
DOI: 10.1007/s40430-017-0730-z
|View full text |Cite
|
Sign up to set email alerts
|

Slip effects on MHD Hiemenz stagnation point nanofluid flow and heat transfer along a nonlinearly shrinking sheet with induced magnetic field: multiple solutions

Abstract: Nowadays, nanofluid (colloidal suspension) gains a lot of interest among various scientists and researchers in different countries due to its vast applications as heat transfer fluid [1], transportation [2, 3], bio-fluid [4], micro-heat sinks [5], micro-transformer [6], etc. Many experiments had been conducted to explore the tremendous heat transfer efficiency of nanofluid (metal and nonmetal nanoparticles) at Argonne National Laboratory, Chicago. The Argonne scientist team revealed that silicon carbide nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…According to (25), we choose the following initial guesses, linear operators and auxiliary functions:…”
Section: Homotopy Analysis Methods (Ham) Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (25), we choose the following initial guesses, linear operators and auxiliary functions:…”
Section: Homotopy Analysis Methods (Ham) Solutionsmentioning
confidence: 99%
“…Abbas et al [24] computed multiple solutions for steady MHD boundary layer stagnation point nano uid ow from a stretching sheet with homogeneous-heterogeneous chemical reactions. Rana et al [25] have used the Lie group analysis to nd similarity transformations for the study of stagnation point ow of nano uid over a nonlinear shrinking surface.…”
Section: Introductionmentioning
confidence: 99%
“…This manifests in a depletion in temperature with stronger suction and an elevation in temperature with stronger injection (blowing). Magnetic induction is indirectly influenced due to coupling of the momentum in equation (17) and induction in equation (18) via a number of terms featuring fluid stream function (and its gradient functions) in the latter and several terms featuring magnetic stream function (and its gradient functions) in the former. With greater momentum slip at the wedge surface (a .…”
Section: Computational Solution With Chebyshev Collocationmentioning
confidence: 99%
“…Numerous investigations have been communicated in recent years with a variety of computational approaches including finite element methods, finite difference methods and symbolic codes for magnetic nanofluid flows. [10][11][12][13][14][15][16][17][18][19][20] Farooq et al 21 used the Mathematica package BVPh 2.0 to analyze MHD Falkner-Skan flow of nanofluid past a fixed wedge in a semi-infinite domain. Rashidi et al 22 studied entropy generation for steady MHD flow past a rotating porous disk in a nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the magnetic and the Casson fluid parameters yield a reduction in the velocity field. Few more studies regarding the flow subject to the MHD can be consulted therein [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%